Evaluation the salivary anti-Porphyromonas gingivalis (IgA and IgG) response in relation to sera levels of Ferritin and Vitamin D in Patients with Beta-Thalassemia Major - misanjas, misanjas; fayiz abd, Shahad; Adel Mahmood, Maha ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Beta-thalassemia major is a severe hereditary anemia that necessitates regular blood transfusions, leading to iron overload. This condition also affects various biological markers, including ferritin and vitamin D levels, and can influence immune responses and oral health. The Aim of Study To examine the relationship between salivary Porphyromonas gingivalis IgA and IgG levels with the concentrations of ferritin and vitamin D in adolescent affected by Beta-Thalassemia Major. A case-control study was conducted from November 2023 to June 2024, involving 45 beta-thalassemia major adolescents and 45 healthy controls. All subjects were within ages ranged between 12-17 years. Saliva sample was collected and analyzed for estimation of salivary anti-Porphyromonas gingivalis IgA and IgG by using ELISA and blood collected and analyzed to measures s.ferritin and s.vitamin D by Cobas E411 system. The study group exhibited significantly lower mean salivary anti-Porphyromonas gingivalis IgA and IgG levels (40.59± 16.71 pg/ml), (15.23±3.21 pg/ml) compared to the control group (93.06± 55.25pg/ml), (18.92±3.32 pg/ml) (p=0.000) respectively. Serum ferritin (4158.37±542.64 ng/ml vs. 25.11±10.93 ng/ml), and vitamin D levels (9.83±4.69 ng/ml vs. 16.40±12.93 ng/ml) showed significant differences (p<0.05) between study and control groups. Beta-thalassemia major significantly impacts salivary and serum biochemical markers, highlighting the importance of regular monitoring and potential targeted therapies to manage iron overload and associated complications. The reduced immune response against Porphyromonas gingivalis in these patients suggests a need for enhanced oral health care and possibly prophylactic measures.